Effect of acute sleep deprivation on heart rate recovery in healthy young adults - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; ATAŞ, HALİL; SARI, İBRAHİM; TİGEN, MUSTAFA KÜRŞAT (SPRINGER HEIDELBERG, 2015)
Sleep deprivation (SD) is known to be associated with increased incidence of adverse cardiovascular events, but underlying pathophysiological mechanism has not been clearly demonstrated. Autonomic nervous system plays an important role in the regulation of cardiovascular function, and impairment in this system is associated with increased cardiovascular mortality. The aim of the current study was to investigate the effect of acute SD on autonomic regulation of cardiac function by determining heart rate recovery (HRR). Twenty-one healthy security officers and nine nurses (mean age 33.25 +/- 8.18) were evaluated. Treadmill exercise test was applied once after a night with regular sleep and once after a night shift in hospital. The HRR was calculated as the reduction in heart rate from peak exercise to the 30th second (HRR30), 1st minute (HRR1), 2nd minute (HRR2), 3rd minute (HRR3), and 5th minute (HRR5). The change in blood pressure (BP) measurements was also determined. Exercise capacity of individuals with SD was significantly lower (10.96 +/- 1.01 vs. 11.71 +/- 1.30 metabolic equivalent task (MET)s; p = 0.002), and peak systolic BP was significantly higher (173.8 +/- 16.3 vs. 166.2 +/- 9.9; p = 0.019). There was a signicant difference in HRR30 (12.74 +/- 6.19 vs. 17.66 +/- 5.46; p = 0.003) and HRR1 (31 +/- 6.49 vs. 36.10 +/- 7.78; p = 0.004). The ratio of these indices to peak HR was also significantly lower with SD (HRR%(30) 8.04 +/- 4.26 vs. 10.19 +/- 3.21; p = 0.025 and HRR%(1): 18.66 +/- 4.43 vs. 20.98 +/- 4.72; p = 0.013). The difference in other indices of HRR was not significant. Our findings suggest that SD blunts cardiovascular autonomic response, and consequences of this relation might be more pronounced in subjects who are exposed to sleeplessness regularly or in subjects with baseline cardiovascular disease.
Keywords: Heart rate recovery; Exercise test; Autonomic dysfunction; Sleep deprivation; Blood pressure; CARDIOVASCULAR-DISEASE; TREADMILL EXERCISE; BLOOD-PRESSURE; NIGHT-SHIFT; STRAIN-RATE; MORTALITY; DYSFUNCTION; METAANALYSIS; ASSOCIATION; DURATION